Preparation and Certification of a Multicomponent Reference Material from Natural Gas Mixture by Gravimetry and Dual GC-FID/TCD System - Shehata, Adel Bassuoni; Askar, Abdulrahman Rashed Al; Ami, Najjy Hamad AlY; Owaysi, Abdullah Suleiman Al (Chemical and Materials Sciences: Developments and Innovations Vol. 6, 2024)
Natural gas (NG) is one of the most important sources of energy for industrial and domestic consumption in the present era because it is cheap and free from sulfur impurities. The processed natural gas consists of methane (main constituent), ethane, propane, and hydrocarbons of heavier molecular masses as well as other gases such as nitrogen, helium, and water vapor. Therefore, accurate and precise measurement of its composition is of fundamental importance for trade reasons. To improve the quality of natural gas measurements, certified reference materials (CRMs) should be used for the calibration of measuring equipment in order to ensure the traceability of the measurement results to the SI units. In the present article, the aim was to prepare and certify a natural gas mixture composed of, helium, hydrogen, nitrogen, methane, ethane, pro-pane, iso-butane, n-butane, iso-pentane, n-pentane and n-hexane. For traceability purposes, a multi-component natural gas mixture was prepared gravimetrically as a reference material according to ISO 6142 from pure helium, hydrogen, n-pentane, i-pentane, n-butane, i-butane, propane, ethane, hexane, methane, and nitrogen. The preparation was done in two dilution steps in 5 L aluminum cylinders. The calculated mole fractions and associated uncertainties of natural gas components were verified by a dual gas chromatography system equipped with a flame ionization detector and thermal conductivity detector (GC-FID/TCD) in accordance with ISO 6143. The GC system was calibrated by a series of primary gas mixtures (CRMs) produced by the National Metrology Institute, NMI. The results obtained by gravimetry and by GC measurements have been checked for compatibility as required by ISO 6142 and were found in very good agreement. Details of the preparation and calculation of the mole fractions and uncertainties of all gas components are explained in this article. The produced natural gas CRM is very important for gas analytical laboratories in calibration and quality control purposes.